Correlation of Serum Creatinine Based on Cockcroft-Gault and CKD-EPI in Diabetes Mellitus - Hasna, Hasna; Kurniawan, Liong Boy; Mangarengi, Fitriani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
World Health Organization (WHO) predicts Indonesia's population with Type 2 Diabetes Mellitus (T2DM) will rise from 8.4 million in 2000 to 21.3 million in 2030. The primary cause of disability and death in people with Diabetes Mellitus (DM) is nephropathy. The early stages of diabetic nephropathy are characterized by glomerular hyperfiltration and an increase in the estimated-Glomerular Filtration Rate (eGFR). Other markers of diabetic nephropathy in addition to eGFR are increased creatinine, albuminuria, and proteinuria. The currently developed formulas for eGFR assessment are the Cockcroft-Gault (CG) formula, the Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease-Epidemiology Collaboration (CKD-EPI). This study aimed to determine the relationship between eGFR using the CKD-EPI formula for serum creatinine and CG in T2DM patients. Fifty-three DM patients participated in a cross-sectional study of the population of patients diagnosed with T2DM by clinicians at Hasanuddin University Hospital between March and June 2022. Version 25 of the Statistical Package for Social Science (SPSS) software was used to analyze the data. Statistical tests for the Normality of data distribution used the Kolmogorov-Smirnov test to determine the normality of data, the ANOVA test was used for comparison, and the Spearman test was used as a correlation test. The relationship between CKD-EPI and CG was highly correlated (r=0.868, p<0.001). Urine albumin levels and eGFR CKD EPI (r= -0.283, p=0.042) and CG (r= -0.282, p=0.043) showed a significant connection. There was a very strong relationship between CKD-EPI and CG.